A people's history of Heaven : a novel - Subramanian, Mathangi, 1980- (Algonquin Books of Chapel Hill, 2019)
"In Bangalore, India, five young women fight to save their homes, which are really only shacks and lean-tos, in a slum named "Heaven," which the city wants to bulldoze in order to accommodate its growing tech industry"--